2006
DOI: 10.1017/s0025315406013786
|View full text |Cite
|
Sign up to set email alerts
|

Assemblages of fish associated with coastal marinas in north-western Italy

Abstract: Assemblages of fish associated with exposed and sheltered sides of breakwaters and adjacent rocky reefs were sampled at coastal marinas on the north-west coast of Italy. Contrary to expectations, assemblages associated with the exposed side of artificial breakwaters did not differ from those at adjacent natural rocky reefs. Assemblages of fish associated with the sheltered side of breakwaters did, however, differ from adjacent rocky reefs and, to a lesser extent from the exposed side of the breakwaters. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 24 publications
2
31
0
Order By: Relevance
“…Estuaries are especially vulnerable to change, as 22 of the world's 32 largest cities are located on estuaries (Ross 1995). Despite the widespread use of shoreline modifications along developed waterfronts, ecological effects of the modifications have only recently been studied, and many SEAWALL AND PIER EFFECTS ON FISH ASSEMBLAGES 815 investigating the effects of shoreline armoring on fish is recent; such studies have used scuba (Clynick 2006;Clynick et al 2008), snorkeling (Toft et al 2007(Toft et al , 2013, enclosure nets (Toft et al 2007), beach seines (Bilkovic and Roggero 2008), and electrofishing (Strayer et al 2012), and the resulting data suggest that land development and changes to shoreline structure influence the composition of nearshore fish species. Seawalls, which are vertical slabs of hard, typically featureless surfaces, are a common type of shoreline armoring, but their effects on fish are not well understood (however, see Toft et al 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…Estuaries are especially vulnerable to change, as 22 of the world's 32 largest cities are located on estuaries (Ross 1995). Despite the widespread use of shoreline modifications along developed waterfronts, ecological effects of the modifications have only recently been studied, and many SEAWALL AND PIER EFFECTS ON FISH ASSEMBLAGES 815 investigating the effects of shoreline armoring on fish is recent; such studies have used scuba (Clynick 2006;Clynick et al 2008), snorkeling (Toft et al 2007(Toft et al , 2013, enclosure nets (Toft et al 2007), beach seines (Bilkovic and Roggero 2008), and electrofishing (Strayer et al 2012), and the resulting data suggest that land development and changes to shoreline structure influence the composition of nearshore fish species. Seawalls, which are vertical slabs of hard, typically featureless surfaces, are a common type of shoreline armoring, but their effects on fish are not well understood (however, see Toft et al 2013).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…What little research has been conducted on marine riprap has revealed somewhat conXicting results and the potential for biogeographic variation certainly exists (Table 1). Some studies report no diVerences in community structure or diversity between riprap and natural rocky habitats (Chapman 2006;Clynick 2006), while others have found clear diVerences for only some taxa (Bulleri and Chapman 2004;Osborn 2005). Some studies have found that riprap supports lower diversity compared to that typical of natural rocky habitats , while others suggest it supports more (Clynick 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies report no diVerences in community structure or diversity between riprap and natural rocky habitats (Chapman 2006;Clynick 2006), while others have found clear diVerences for only some taxa (Bulleri and Chapman 2004;Osborn 2005). Some studies have found that riprap supports lower diversity compared to that typical of natural rocky habitats , while others suggest it supports more (Clynick 2006). Recent studies also suggest that anthropogenic structures favor invasive species over native ones (Wasson et al 2005;Glasby et al 2007;Tyrrell and Byers 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies has compared benthic assemblages on different types of artificial habitats (Connell and Glasby, 1998;Connell, 2001) or have assessed the extent to which artificial structures can be considered as surrogates of natural rocky habitats, focusing on assemblages of 35 algae, invertebrates or fish (Connel and Glasby, 1998;Glasby, 1999;Davis et al 2002;Chapman, 2003;Chapman and Bulleri, 2003;Guidetti, 2004;Chapman 2006;Clynick, 2006). To our knowledge, very few studies have instead assessed the ecological implications of introducing hard coastal-defence structures into areas where soft-bottoms are predominant (but see Davis et al, 2002, Bacchiocchi andAiroldi, 2003;Moschella et al, 2005;Pinn et al, 2005;Gacia et al, 2007).…”
Section: Introductionmentioning
confidence: 99%